Classroom behaviour a practical guide to effective teaching, behaviour management and colleague support - Rogers, Bill 1947- (SAGE, 2015)
"This book looks at the issues facing teachers working in today's classrooms. Describing real situations and dilemmas, Bill Rogers offers his advice on dealing with the challenges of the job, and how building a rapport with both students and colleagues can support good practice."--Back cover.